Interaction of Bordetella adenylate cyclase toxin with complement receptor 3 involves multivalent glycan binding - Hasan, Shakir; Osickova, Adriana; Bumba, Ladislav; Novák, Petr; Sebo, Peter; Osicka, Radim (FEBS letters, 2015)
The interaction of Bordetella pertussis adenylate cyclase toxin (CyaA) with complement receptor 3 (CR3, CD11b/CD18) involves N-linked oligosaccharide chains. To investigate the relative importance of the individual N-glycans of CR3 for toxin activity, the asparagine residues of the consensus N-glycosylation sites of CR3 were substituted with glutamine residues that cannot be glycosylated. Examination of CR3 mutant variants and mass spectrometry analysis of the N-glycosylation pattern of CR3 revealed that N-glycans located in the C-terminal part of the CD11b subunit are involved in binding and cytotoxic activity of CyaA. We suggest that these N-glycans form a defined clustered saccharide patch that enables multivalent contact of CR3 with CyaA, enhancing both affinity and specificity of the integrin-toxin interaction.
Keywords: CD18 Antigens; makrofágový antigen 1; Protein Structure, Tertiary; Glycosylation; CD11b Antigen; substituce aminokyselin; glutamin; Adenylate Cyclase Toxin; Bordetella pertussis; polysacharidy; terciární struktura proteinů; lidé; Amino Acid Substitution; Polysaccharides; Glutamine; asparagin; Macrophage-1 Antigen; glykosylace; antigeny CD18; Asparagine; antigeny CD11b; adenylátcyklasový toxin; Humans